Increased Temperature and Protein Oxidation Signal HSP72 mRNA and Protein Accumulation in the In Vivo Exercised Rat Heart - Staib, Jessica L. (2008)
Myocardial heat shock protein 72 (HSP72) expression, mediated by its transcription factor heat shock factor 1 (HSF1), increases following exercise. However, the up-stream stimuli governing exercise-induced HSF1 activation and subsequent HSP72 gene expression in the whole animal remain unclear. Exercise-induced increases in body temperature may promote myocardial radical production leading to protein oxidation. Conceivably, myocardial protein oxidation during exercise may serve as an important signal promoting nuclear HSF1 migration and activation of HSP72 expression. Therefore, these experiments tested the hypothesis that preventing exercise-induced increases in body temperature attenuates cardiac protein oxidation, diminishes HSF1 activation and decreases HSP72 expression in vivo. To test this hypothesis, in vivo exercise-induced body temperature was manipulated by exercising male rats in either cold (4°C) or warm (22°C) ambient conditions. Warm exercise increased both body temperature (+ 3°C) and myocardial protein oxidation whereas these changes were attenuated by cold exercise. Interestingly, exercise in both conditions did not significantly increase myocardial nuclear localized phosphorylated HSF1. Nonetheless, warm exercise elevated left-ventricular HSP72 mRNA by 9-fold and increased myocardial HSP72 protein levels by 3-fold compared to cold-exercised animals. Collectively, these data indicate that elevated body temperature and myocardial protein oxidation promoted exercise-induced cardiac HSP72 mRNA expression and protein accumulation following in vivo exercise. However, these results suggest that exercise-induced myocardial HSP72 protein accumulation is not a result of nuclear-localized, phosphorylated HSF1 indicating that other transcriptional or posttranscriptional regulatory mechanisms are involved in exercise-induced HSP72 expression.